Rebleeding after Stent Grafting for the Celiac Artery Bleeding following Extended Pancreaticoduodenectomy. (8th December 2013) - Ohta, Kengo; Shimohira, Masashi; Hashizume, Takuya; Kawai, Tatsuya; Muto, Masahiro; Honda, Junichi; Shibamoto, Yuta
Abstract : We report a 74-year-old man with rebleeding following stent grafting for the celiac artery bleeding which developed after extended pancreaticoduodenectomy for cancers of the bile duct and stomach. The site of rebleeding seemed to be different from the site of the first bleeding, so it was considered not an endoleak but a new bleeding. It was successfully treated by placement of another stent graft.